2004
DOI: 10.1021/jo0489418
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Catalyzed Reactions of Aromatic Aldehydes with Ethyl Diazoacetate:  An Investigation on the Synthesis of 3-Hydroxy-2-arylacrylic Acid Ethyl Esters

Abstract: Several commercial Lewis acids, including those of the Bronsted type, specifically HBF(4).OEt(2), are able to catalyze the reaction between aromatic aldehydes and ethyl diazoacetate to produce 3-hydroxy-2-arylacrylic acid ethyl esters and 3-oxo-3-arylpropanoic acid ethyl esters. Reactions catalyzed by the iron Lewis acid [(eta(5)-C(5)H(5))Fe(+)(CO)(2)(THF)]BF(4)(-) (i.e., 1) have the best yields and greatest ratio of 3-hydroxy-2-arylacrylic acid ethyl ester. The product distribution of 1 is not affected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…37 This reaction is believed to proceed through an addition/hydride migration route. Hossain and co‐workers described trends across a range of Lewis acids and Brønsted acids, and revealed that in contrast to the selectivity for β‐ketoester provided by SnCl 4 , many other Lewis acids and HBF 4 ⋅OEt 2 provided either low selectivity, or favored a 3‐hydroxy acrylate product 38…”
Section: Brønsted Acid “Compatibility” With Diazo Compoundsmentioning
confidence: 99%
“…37 This reaction is believed to proceed through an addition/hydride migration route. Hossain and co‐workers described trends across a range of Lewis acids and Brønsted acids, and revealed that in contrast to the selectivity for β‐ketoester provided by SnCl 4 , many other Lewis acids and HBF 4 ⋅OEt 2 provided either low selectivity, or favored a 3‐hydroxy acrylate product 38…”
Section: Brønsted Acid “Compatibility” With Diazo Compoundsmentioning
confidence: 99%
“…The cationic complexes of type, [CpFe(CO) 2 L] + (L = labile ligand) [1][2][3][4] are an important class of transition metal compounds that have been extensively utilized in synthesis [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and catalysis [3,14,[22][23][24][25][26][27][28][29][30][31][32][33]. A particular example is the ethereal complex, [CpFe-(CO) 2 (THF)]BF 4 [34] in which the labile tetrahydrofuran (THF) is coordinated to the metal centre through the oxygen atom.…”
Section: Introductionmentioning
confidence: 99%
“…A particular example is the ethereal complex, [CpFe-(CO) 2 (THF)]BF 4 [34] in which the labile tetrahydrofuran (THF) is coordinated to the metal centre through the oxygen atom. This complex has been proven to be an essential precursor in the synthesis of various cyclopentadienyliron complexes [4,[10][11][12][13][15][16][17][18][19][20]35], as well as catalysts in various organic syntheses such as the [2+2] cycloaddition of alkenes [36], Diels-Alder reactions [37,38], cyclopropanation [27,[31][32][33], epoxidation [29,30] and aziridination [25][26][27][28], among others [3,[22][23][24]27,29,39]. In all these reactions THF is easily displaced by the desired substrate to form either the desired intermediate or desired end product.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of catalyst deactivation is remarkable as amine complexes of Fp + are known and can be prepared from [Fp(Et 2 O)][BF 4 ] and alkylamines 25. On the other hand, it has been reported that Fp + also acts as a catalyst in the presence of 1,8‐bis(dimethylamino)naphthalene, which is potentially able to deactivate it 26…”
Section: Resultsmentioning
confidence: 99%